Bone-anchored titanium implants for auricular rehabilitation: case report and review of literature - Gumieiro, Emne Hammoud; Dib, Luciano Lauria; Jahn, Ricardo Schmitutz; Santos Junior, João Ferreira dos; Nannmark, Ulf; Granström, Gösta; Abrahão, Márcio (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Osseointegrated implants have acquired an important role in the prosthetic rehabilitation of patients with craniofacial defects. The main indications are lack of local tissue for autogenous reconstruction, previous reconstruction failure and selection of this technique by the patient. This paper presents a clinical case and discusses indications and advantages of the osseointegrated implant technique for retention of auricular prostheses. TYPE OF STUDY: Case report, Universidade Federal de São Paulo (UNIFESP). METHODS: A female patient received three auricular implants after surgical resection of a hemangioma in her left ear. The time taken for osseointegration of the temporal bone was three months. After fabrication of the implant-retained auricular prosthesis, the patient was monitored for 12 months. RESULTS: The clinical parameters evaluated showed good postoperative healing, healthy peri-implant tissue, good hygiene and no loss of implants. Good hygiene combined with thin and immobile peri-implant soft tissues resulted in minimal complications. Craniofacial implant integration appears to be sitedependent; increasing age affects osseointegration in the temporal bone. The frequency of adverse skin reactions in peri-implant tissues is generally low. CONCLUSION: The surgical technique for rehabilitation using implant-retained auricular prostheses seems to be simple. It is associated with low rates of adverse skin reactions and long-term complications. Prostheses anchored by osseointegrated implants seem to provide better retention than do prostheses supported on spectacle frames, less risk of discoloration through the use of adhesives and better esthetic results than do prostheses anchored in the surgical cavity.